EXPERIMENTAL RESEARCH ON PENETRATION RESISTANCE OF ALUMINUM ALLOY FOAM SANDWICH PANEL AGAINST HEMISPHERICAL-NOSED PROJECTILE (MT) - ZHANG TieChun; ZENG XianZhi; FENG ZhengXing; DENG YunFei (Jixie qiangdu)
In order to study the effect of PMI foam on the impact resistance of the double-layered plates of aluminum alloy 2 A12-T4, the high-velocity impact experiments were performed to the aluminum alloy double-layered plates and aluminum alloy/PMI/aluminum alloy sandwich panel by using hemispherical-nosed projectiles launched by the one-stage gas gun system. The ballistic limit velocity and damage characteristics of the plates were obtained through the experimental results. The results show that the PMI foam core can restrict the plastic deformation of aluminum alloy plate under the same thickness as the aluminum alloy plate, decrease the absorption of impact energy and reduce the impact resistance of the aluminum alloy 2 A12-T4 double-layered plates by increasing the rigidity of the plate. In addition, the effect of the PMI foam core on the impact resistance of the plates decreases as the increase of velocity of the projectile.